Endometrial glandular changes in aged captive cheetahs (Acinonyx jubatus) in southern Africa - Hartman, Marthinus Jacobus (University of Pretoria, 2024)
Mini Dissertation (MMedVet (Pathology))--University of Pretoria, 2021.